Can player tracking devices monitor changes in internal response during multidirectional running? - Oxendale, C. L.; Highton, J.; Smith, G.; Twist, C. (Research Quarterly for Exercise and Sport, 2023)
Purpose: We examined the movement, physiological and muscle function responses to running with and without (i.e. linear) multiple directional changes to understand which measures of external demands better reflected changes in the internal response.